Gingerenone A Attenuates Monocyte‐Endothelial Adhesion via Suppression of I Kappa B Kinase Phosphorylation. Issue 1 (4th October 2017) - Kim, Hee Joo; Son, Joe Eun; Kim, Jae Hwan; Lee, Charles C.; Yang, Hee; Yaghmoor, Soonham Sami; Ahmed, Youssri; Yousef, Jehad Mustafa; Abualnaja, Khalid Omer; Al‐Malki, Abdulrahman Labeed; Kumosani, Taha Abdullah; Kim, Jong Hun; et al.
ABSTRACT: During the early stages of atherosclerosis, monocytes bind and migrate into the endothelial layer, promoting inflammation within the aorta. In order to prevent the development of atherosclerosis, it is critical to inhibit such inflammation. The therapeutic effects of ginger have been investigated in several models of cardiovascular disease. However, although a number of previous studies have focused on specific compounds, the mechanisms of action responsible remain unclear. Here, we investigated five major compounds present in ginger, and observed that gingerenone A exhibited the strongest inhibitory effects against tumor necrosis factor (TNF)‐α and lipopolysaccharide (LPS) induced monocyte‐endothelial adhesion. Furthermore, gingerenone A significantly suppressed the expression of TNF‐α and LPS‐induced vascular cell adhesion molecule‐1 (VCAM‐1) and chemokine (C‐C motif) ligand 2 (CCL2), key mediators of the interaction between monocytes, and endothelial cells. Transactivation of nuclear factor‐κB (NF‐κB), which is a key transcription factor of VCAM‐1 and CCL2, was induced by TNF‐α and LPS, and inhibited by treatment of gingerenone A. Gingerenone A also inhibited the phosphorylation of NF‐κB inhibitor (IκB) α and IκB Kinase. Taken together, these results demonstrate that gingerenone A attenuates TNF‐α and LPS‐induced monocyte adhesion and the expression of adhesion factors in endothelial cells via the suppression of NF‐κB signaling. J. Cell. Biochem. 119: 260–268, 2018. © 2017 Wiley Periodicals, Inc. Abstract : Gingerenone A attenuates TNF‐α and LPS induced monocyte adhesion and the expression of adhesion factors in endothelial cells. Gingerenone A appears to have therapeutic implications for the prevention of atherosclerosis.